2021
DOI: 10.1186/s12889-021-12002-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of total pre-existing comorbidities with stroke risk: a large-scale community-based cohort study from China

Abstract: Background Comorbidities, any other coexisting diseases in patients with a particular index disease, are known to increase the mortality of a stroke. However, the association of pre-existing comorbidities with stroke risk has not been fully studied. Methods This study included 16,246 adults from a prospective community-based cohort with a baseline survey conducted in 2013 in China. Participants were followed up with hospitalization records and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…[ 22 ] Another study reported that DM, hypertension, previous stroke, and heart disease were all significantly and positively linked to the mortalityof stroke. [ 23 ] In the present study, anterior circulator stroke was the commonest type of stroke in survivors as well as non-survivors. Studies have shown that patients with extensive infarcts involvingthe middle cerebral artery have been found to have a mortality rate of up to 78%.…”
Section: Discussionmentioning
confidence: 73%
“…[ 22 ] Another study reported that DM, hypertension, previous stroke, and heart disease were all significantly and positively linked to the mortalityof stroke. [ 23 ] In the present study, anterior circulator stroke was the commonest type of stroke in survivors as well as non-survivors. Studies have shown that patients with extensive infarcts involvingthe middle cerebral artery have been found to have a mortality rate of up to 78%.…”
Section: Discussionmentioning
confidence: 73%
“…Hypertension was defined as mean systolic/diastolic blood pressure ≥140/90 mm Hg or use of antihypertensive medications [31]. Participants were considered to have diabetes if they reported a personal history of diabetes, used hypoglycemic drugs, or possessed a fasting blood glucose level of ≥7.0 mmol/L [24]. Hyperlipidemia was determined if participants responded “yes” to the question “Has a doctor ever told you that you suffered from hyperlipidemia?”, self‐reported history of lipid‐lowering treatment, or laboratory measurement (TC >6.20 mmol/L, TG >2.30 mmol/L, or HDL‐C <1.00 mmol/L).…”
Section: Methodsmentioning
confidence: 99%
“…The details for recruitment, study design, and other characteristics of the Prospective Follow-up Study on Cardiovascular Morbidity and Mortality in China have been previously described [23][24][25]. Briefly, the baseline survey was launched in 2013 in Changshu, Eastern China, and eligible participants aged 35-74 years were included.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…As these risk factors accumulate with age, the elders are more likely to have a stroke 11 . It is shown that the number of comorbidities is independently associated with higher stroke occurrence and the combination of older age and more comorbidities leads to a higher risk of stroke 10 . Meanwhile, comorbidities imply more pharmacological treatment and lead to a higher risk of adverse events, therefore a worse stroke prognosis 12,13 .…”
Section: Introductionmentioning
confidence: 99%